2017
DOI: 10.5326/jaaha-ms-6500
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Axillary and Auricular Temperature with Rectal Temperature in Systemically Healthy Dogs Undergoing Surgery

Abstract: Obtaining a patient's temperature is an important part of a patient's physical examination. As human medicine transitions to noninvasive temperature measurements, so does veterinary medicine. Historically, temperature measurement has been obtained from rectal readings; however, alternative methods, such as axillary and auricular temperatures, are increasing in popularity. The purpose of the study was to compare these alternative techniques to the gold standard of rectal temperature. Temperatures were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
1
17
2
Order By: Relevance
“…Mathis and Campbell (2015) found that temperature taken from dogs from an uncontrolled temperature environment exhibited inconsistent axillary measurement readings. A third study looked at dogs of assorted breeds (n = 50) admitted for various surgical procedures, such as tibial plateau leveling osteotomy, percutaneous laser disk ablation, and Hemilaminectomy (Cichocki et al, 2017). The dogs had axillary and rectal temperatures taken three times, once on the day of admittance into the hospital, once after the dog had recovered from surgery, and once more on the day the animal was discharged (Cichocki et al, 2017).…”
Section: Instrumentationmentioning
confidence: 99%
See 4 more Smart Citations
“…Mathis and Campbell (2015) found that temperature taken from dogs from an uncontrolled temperature environment exhibited inconsistent axillary measurement readings. A third study looked at dogs of assorted breeds (n = 50) admitted for various surgical procedures, such as tibial plateau leveling osteotomy, percutaneous laser disk ablation, and Hemilaminectomy (Cichocki et al, 2017). The dogs had axillary and rectal temperatures taken three times, once on the day of admittance into the hospital, once after the dog had recovered from surgery, and once more on the day the animal was discharged (Cichocki et al, 2017).…”
Section: Instrumentationmentioning
confidence: 99%
“…Core temperature is considered the gold standard of body temperature, as it closely reflects the temperature of the internal organs (Allegaert et al, 2014). The temperature at the hypothalamus is also a desired location to monitor, as this region is where body temperature is perceived (Cichocki et al, 2017). However, clinically, the most conventional method of taking a canine's temperature is through the rectal mucosa, as it continues to be a minimally invasive method that provides insight to core temperature (Kreissl and Neiger, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations